Effect of SOYXYL as a Dietary Protected Protein Supplement on the Reproductive Performance of Simmental Bulls - Prasetiyono, Bambang Waluyo Hadi Eko; Widiyanto, Widiyanto; Ondho, Yon Soepri; Subrata, Agung; Widodo, Hermawan Setyo (Faculty of Animal Science, Jenderal Soedirman University in associate with Animal Scientist Society of Indonesia (ISPI), 2020)
The study aimed to evaluate the effect of SOYXYL as one of the dietary protected protein supplement product in the rations on the reproduction performance of Simmental bulls. Twelve 5 years-old Simmental bulls were allotted to 4 treatment groups with 3 replications in each, i.e.: T0= control ration (elephant grass + 5 kg/head/day commercial concentrate), T1= control ration + 150 g protected protein supplement SOYXYL (3% of concentrate), T2 = control ration + 300 g SOYXYL (6% of concentrate) and T3= control ration + 450 g SOYXYL (9% of concentrate). The experiment lasted for 90 days. At the end of the experiment, semen and blood were collected and body weight gain was measured. The variables measured included sperm motility, sperm concentration, blood protein, blood urea and the concentration of testosterone. Results showed that SOYXYL supplementation, particularly at the levels of 3 and 6%, increased the total plasma protein of bulls. SOYXYL supplementation at 3% from concentrate resulted in increased plasma urea concentration. Feeding SOYXYL, particularly at the levels of 6 and 9%, increased the average daily gain of bulls as compared to control. Feeding 3% SOYXYL increased, but at the levels of 6 and 9% decreased the concentration of sperm of bulls. The concentration of testosterone was higher in the bulls received 3 and 6% SOYXYL in the rations. Dietary supplementation of SOYXYL increased the sperm motility of Simmental bulls. In conclusion, dietary supplementation of SOYXYL at the level of 3% increased plasma protein, testosterone, and sperm concentrations as well as sperm motility. However, supplementation of SOYXYL at 6 and 9% from rations decreased the concentrations of sperm and testosterone.